Randomized Double Blinded Placebo Controlled Trial Comparing Diclofenac and Piroxicam in Management of Acute Renal Colic and Its Clinical Implications - KandaSwamy, Gokul Vignesh; Dhanasekaran, Ananda Kumar; Elangovan, Aravindhan; John, Bobby; Viswaroop, Bobby; Vedanayagam, Kandasami Sangam (Urology Journal, 2015)
Purpose: To compare the efficacy of sublingual piroxicam 40 mg with intramuscular diclofenac 75 mg in treatment of acute renal colic. The secondary objective was to look for factors that can affect the severity of the pain and pain relief in acute renal colic. Materials and Methods: One hundred patients with acute renal colic were randomized into two groups. Group A (n = 50) received intramuscular diclofenac and sublingual methylcobalamin. Group B (n = 50) received sublingual piroxicam 40 mg and intramuscular distilled water. Pain severity was measured using Visual Analog Scale (VAS) and verbal and facial response scales. They were followed up for 3 h. Intramuscular injection of pentazocine 30 mg with promethazine 25 mg were used as rescue drugs. Results: Both groups were comparable for age, sex distribution, body mass index (BMI), and pain duration before presentation. Significant pain relief was noticed in both groups. Sixteen percent in group A and 18% in group B had complete pain relief within 30 min (P = .75). Fifteen patients in group A and 13 patients in group B needed rescue drugs, 84% of group A and 76% of group B had complete pain relief at the end of 3 hours (P = .25). Decrease in pain by each scoring method was also comparable (P = .75). In multiple regression analysis, increasing age, positively affects the severity of pain and pain relief while increasing BMI negatively affect the initial pain relief. Acute renal colic seems to affect men more commonly than women, 81% of the study population were men. Patients with low initial pain score did not require any additional pain relief. Average pain duration before presenting to hospital is 260 min. Sixty percent of renal colics are due to stones below pelvic brim. Conclusion: The results show that sublingual piroxicam is as effective as intramuscular diclofenac. It can be easily self-administered and it overcomes the morbidity and time delay in getting intramuscular diclofenac.